2012
DOI: 10.5539/res.v4n4p45
|View full text |Cite
|
Sign up to set email alerts
|

Twinship and Marriage – Experiences during the Course of Twin

Abstract: The aim of this study was to explore and describe older twins' experiences of their marriages in relation to the co-twin relationship. Material and Methods:The material consisted of 34 life story interviews with older twins (70+), representing various experiences of twinship and marriage. The data was analysed with qualitative latent content analysis.Results: Phases of marriage describe the time of Courtship -partners were chosen based on infatuation. Most were non-related, but some were relatives or friends. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This finding has several important implications for research on close relationships. For example, the strong relationship between twins --especially MZ twins --might cause conflicts in close relationships, especially when the romantic partner expects to be the first in the attachment hierarchy (Pietilä, Bülow, & Björklund, 2012). Petersen, Martinussen, McGue, Bingley, and Christensen (2011) found that twins are less likely to marry and have lower divorce rates than non-twin siblings.…”
Section: Discussionmentioning
confidence: 99%
“…This finding has several important implications for research on close relationships. For example, the strong relationship between twins --especially MZ twins --might cause conflicts in close relationships, especially when the romantic partner expects to be the first in the attachment hierarchy (Pietilä, Bülow, & Björklund, 2012). Petersen, Martinussen, McGue, Bingley, and Christensen (2011) found that twins are less likely to marry and have lower divorce rates than non-twin siblings.…”
Section: Discussionmentioning
confidence: 99%
“…102 More importantly, many twins view their connection with their twin, which can be 'as close, bonded, and nurturing as many romantic relationships', 103 to be equal to their marital relationship. 104 Consequently, if Niankhkhnum and Khnumhotep were twins, their connection with one another will likely have overshadowed their associations with their wives and children, as their decorative programme appears to confirm.…”
Section: Characteristics Of Twinsmentioning
confidence: 99%